(untitled) (Avocetta, 2023)
The aim of this work was to monitor the waterbird community throughout the year in an anthropized peri-urban wetland of Florence province. The sampling was conducted from January 2018 to December 2020 throughout all seasons of the year by direct observations, using binoculars and acoustic surveys. To evaluate bird biodiversity, we calculated the relative frequency, abundance and species richness, the Shannon-Wiener Index and evenness. We monitored 19 species, among which six were dominant species: Anas platyrhynchos, Larus michahellis, Fulica atra, Podiceps cristatus, Aythya ferina, Chroicocephalus ridibundus. Abundance, species richness and Shannon-Wiener diversity were highest in winter, while evenness was highest in spring; a Principal Component Analysis confirmed that Arnovecchio is an important wetland both for breeding (Podiceps cristatus, Tachybaptus ruficollis, Anas platyrhynchos) and wintering species (Aythya ferina, Chroicocephalus ridibundus). Most of the species were identified in autumn and in winter when this area may represent for some birds a protected refuge during the hunting season. Among the most observed species, Aythya ferina and Chroicocephalus ridibundus were absent in spring but were more common in winter. Among the nesting species, the most common are Podiceps cristatus and Tachybaptus ruficollis. The results of this study suggest a constant presence of birds during the whole year in this peri-urban area, thereby highlighting its relevance for biodiversity as well as for providing the opportunity to human visitors to enjoy its natural values in all seasons.